The Effect of Predict-Observe-Explain (POE) Strategy on Students’ Conceptual Mastery and Critical Thinking in Learning Vibration and Wave - Dandy Furqani; Selly Feranie; Nanang Winarno (Journal of Science Learning, 2018)
Scientific learning in schools requires not only students’ ability to understand concept, but also critical thinking abilities of the students. However, the current scientific learning process is still focused on only cognitive aspects. Therefore, a teaching model or strategy that is able to support students to understand concept as well as develop students’ critical thinking abilities is needed. One of the existing needed strategies is Predict-Observe-Explain (POE). The aim of this research is to identify the effects of Predict-Observe-Explain (POE) strategy on students’ conceptual mastery and critical thinking in learning vibration and wave. The method that was used in this research was weak experiment and the design was one-group pretest-posttest. The population of this research was 8th grader students in a junior high school in Bandung. The sample of the research was 18 students. The technique that was used was purposive sampling. The results of the research were: There was enhancement in students’ conceptual mastery, indicated by average normalized gain of 0,29; There was enhancement in students’ critical thinking abilities from level 1,30 (challenged thinker) to 2,07 (beginning thinker). Students can easily predict, observe and explain waves concept have difficulties on transversal waves and longitudinal waves concepts. For the next research it is recommended that Predict-Observe-Explain (POE) is to be tried on motion, electricity and ecosystem.